Strongyloides stercoralis infestation in an onco-haematogenic patient - Carlotta Guidetti; Francesco Merli; Luigi Vecchia (Microbiologia Medica, 2010)
We describe a case of an infection caused by Strongyloides stercoralis in a patient affected by onco-haematological disease, who manifested an high peripheral hypereosinophilia after a few cycles of specific chemotherapy.